التأصيل والقياس المحاسبي لرأس المال البشري في منظمات الأعمال الحديثة - حـاج قـويدر, ڤـورين (Recherches économiques et managériales; Vol. 15 (2014): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES(JUIN), 2014)
ملخص: يناقش هذا البحث مفهوم محاسبة الموارد البشرية ومدى إمكانية اعتبار المورد البشري أصل قابل للقياس مثل باقي الأصول الأخرى الموجودة في المنظمة، مع إبراز بعض الطرق والأساليب المستعمل في منظمات الإعمال الحديثة لقياس قيمة المورد البشري، وكذا طرق إهتلاك هذا المورد باعتباره أصل قابل للقياس والتناقص عبر الزمن. Abstract:   Discusses This research concepts associated with human resources accounting and the possibility of considering human resource out of a measurable like the rest of the other assets in the enterprise, while highlighting some of the methods and techniques used in business organizations of modern measuring the value of human resource, as well as methods of amortization of this resource as the origin of a measurable and decreasing crosstime.